Online Political Campaigns: A Case Study of the General Election in Three Southern Provinces of Thailand - tuansiri, ekkarin (King Prajadhipok’s Institute Journal, 2021)
Nowadays, social media is a part of people’s lives at all levels of society and in all aspects of life. In elections, Facebook is used as a medium to connect political parties and voters. In Thailand’s 2019 general election, the three biggest political parties that competed in the Deep South used this new media. This research found that the Future Forward party used Facebook for their online campaigns equally together with offline campaigns because they were brand-new and lacked constituents. Meanwhile, Pheu Thai and Prachachat party used Facebook as augmentation since they had roots in the area. Facebook has been used for political advertising because of its convenient functions to make attractive and simple content, so parties could select issues and tools to deliver their content.